Women's Political Participation In The 2020 Regional Head Elections (Case Study In Berkas Subdistrict Of Teluk Segara, Bengkulu City): Partisipasi Politik Perempuan Dalam Pemilihan Umum Kepala Daerah Tahun 2020 (Studi kasus di Kelurahan Berkas Kecamatan Teluk Segara Kota Bengkulu) - Kencana N., Agnesya Putri; Harmiati, Harmiati; Darmawi, Edi (JURNAL ISIP VOICE : Jurnal Ilmu Sosial dan Ilmu Politik, 2024)
This research aims to find out and understand women's political participation in the 2020 Regional Head elections in The Village File Of Teluk Segara Subdistrict, Bengkulu City. The method used is descriptive qualitative with in-depth interview data collection techniques, observation/experience, and documentation. Informants numbered 9 women consisting of PKK mothers, pps members 2 people, village staff, and 5 housewives.Based on the results of the study, it can be concluded that women's political participation in the 2020 Regional Head elections in The Village file of Teluk Segara Subdistrict in Bengkulu city is quite high. This can be seen from the awareness of the women to participate in the general election of the Regional Head. The form of women's participation in political activities in the form of active as voters, following government discussions and also socialization. Factors that affect the level of women's participation in the 2020 Regional Head elections are social and economic status, political situation, political awareness, trust in the government, and political stimulants. . The factors that influence them the most are the political awareness factors in which there is already a direction and data collection of the government on the existence of elections there is a growing sense of responsibility from within to participate in political discussions, become a member of the vote, and become a voter who has been recorded as a Permanent Voter List (DPT)